Nasilje: cinizem javnega govora - Turk, Aleksandra (Teorija in praksa, 1997)
There is a lot of violence towards women and children in our country, but the victims are usually silent. They rarely find the right person to turn to. They are afraid to testify in court, one of the reasons being the leniency of courts in Slovenia towards the violators. Legal experts are aware of this and have been trying to change the penal code for years. They also stress that doing time in prison does not have the right effect and that violators should be included in a special programme of treatment. Attempts are directed at opening victim shelters. This is also the goal of the Centre of Social Workers in Maribor, whose employees have overcome numerous difficulties and, with the aid of the Ministry of Work, Family and Social Issues, opened such a safe house - the only one of its kind in Slovenia.
Keywords: javno obveščanje; množično komuniciranje; sexual intercourse; spolnost; woman; ženske; žrtve; nasilje; spolno nasilje; viktimizacija; objektivnost